An educational workshop on sport as a tool for cultural enhancement in Italian lower secondary schools - Scala, Giovanna; Palmiero, Fabiola; Tafuri, Maria Giovanna; Di Palma, Davide; Romano, Generoso (SPORT TK-EuroAmerican Journal of Sport Sciences, 2026)
This experimental study aimed to examine the effectiveness of a cricket-based sports workshop designed to promote the educational and cultural inclusion of students of Sri Lankan origin in an Italian lower secondary school. The study involved 60 students (aged 12–13 years) enrolled in two second-year classes of a public lower secondary school in Emilia-Romagna, equally divided into an experimental group (n = 30) and a control group (n = 30). Each group included 15 students of Sri Lankan origin and 15 Italian or other students, ensuring balanced cultural composition. The experimental group participated in a six-week intercultural sports workshop based on cricket (12 sessions, 18 hours total), while the control group followed the regular physical education curriculum without specific intercultural content. A mixed-methods approach (quantitative and qualitative) was adopted, combining standardised questionnaires assessing school belonging, ethnic identity and peer relationships with semi-structured interviews and systematic observations. The results indicate significant improvements in the experimental group (p<0.05) in terms of sense of belonging to the school, perception of cultural identity, and quality of peer relationships, whereas no significant changes were observed in the control group (p>0.05). Overall, the findings suggest that integrating culturally meaningful sports activities into school-based educational programmes can be an effective strategy for fostering social cohesion, intercultural dialogue and inclusive school climates, benefiting both students from migrant backgrounds and the wider school community.